Ball flower like manganese, strontium substituted hydroxyapatite/cerium oxide dual coatings on the AZ91 Mg alloy with improved bioactive and corrosion resistance properties for implant applications. Issue 35 (18th April 2015) - Gopi, D.; Murugan, N.; Ramya, S.; Shinyjoy, E.; Kavitha, L.
<x xml:space="preserve">Abstract</x> Mn, Sr-HAP/CeO2 dual layer coated AZ91 Mg alloy will be a revolutionary potential material for orthopedic implants.